PEMBUATAN ARANG AKTIF DARI TEMPURUNG BIJI-BIJIAN ASAL TANAMAN HUTAN DAN PERKEBUNAN - Nurmala Hudaya; Hartoyo Hartoyo (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
Research on µtilization of several seed shells of Aleurites moluccana, Hevea brasiliensis, Canarium communne L and Cocos nucifera for activated carbon by means of steam or ZnCl2 solution activat.ionwas conducted at the Forest• Product• Beaearch and Development Centre, Bogor.The results1howed that all kinds of raw material used could produce good quality and high yield of activated carbon. The yield of activated carbon produced were re1pectively ranging 'from 81,1-87,0% (Qmarium communne L.),66,4-77,1% (Aleurites moluecana), 65,3-71,3% (Hevea brasiliensis), 65,7-77,3% Cocosnucifera). The quality of activat- ed carbon determened by adBorptive capacity of Iodine number need the• requirement as specified Standard of A WWA (1978) i.e minimum 500 mg/g.",